ALIH KODE DALAM PERCAKAPAN MAHASISWA FAKULTAS ILMU BUDAYA UNIVERSITAS HALU OLEO - Nursan.et.al; Wa Ode Halfian (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2024)
This research is entitled "Code-Switching in Student Conversations of the Faculty of Cultural Sciences, Halu Oleo University". The purpose of this study is to describe the forms of code switching and the factors that cause code switching in student conversations of the Faculty of Cultural Sciences, Halu Oleo University. The method used is descriptive qualitative method. The data collection used in this study were observations, records, notes, and interviews. Data analysis techniques were carried out with data transcription, identification or marking of data, data classification, data description, and concluding research results. Based on the results of the research conducted, it was found that the forms of code switching in the conversations of students of the Faculty of Cultural Sciences were internal code switching from Indonesian to Muna language and internal code switching from Muna language to Indonesian. Factors causing code switching in student speech are influenced by the speaker, the interlocutor, changes in the situation with the presence of a third person, and changes in the topic of conversation.